Emergência de sida rhombifolia l. em diferentes épocas e profundidades de semeadura - Parreira, Mariana Casari [UNESP]; Mastrotti Pereira, Fernada Campos [UNESP]; da Costa Aguiar Alves, Pedro Luis [UNESP] (Universidade Federal de Uberlândia (UFU), 2012)
The major problems in pasture areas are weed management. Sida rhombifolia L. is a major weed of these areas, causing serious problems for the farmers. This research aimed to understand the importance of Sida rhombifolia L. seed depth in the soil profile to increase the germination rate and seedling emergence potential. During the month of September 2008 (spring) and January 2009 (summer), two assays were carried out under greenhouse conditions and the seeds were sown at 0, 1, 2, 3, 4, and 5 cm from the soil surface. The experiment was conducted in pots, 5 L, with 5 replicates containing 50 seeds per pot. In both seasons, the emergence percentage and germination speed were increasing until the 17th day after sowing, and the depths of one, two and three centimeters were those which obtained higher emergencies and germination speed. In one cm depth, the germination was 28% and 32% in spring and summer, respectively, statistically different from the other depths. however, five depths centimeters; the germination was only 8% and 13% respectively.
Emergence of sida rhombifolia l. at different seasons and depth
Keywords: Sida rhombifolia L; Weed; Germination; Reproductive biology